Numerical simulation of electromagnetic coupling in explicitly meshed wiring looms and bundles - Meng, Xuesong; Sewell, Phillip; Vukovic, Ana; Zhang, Zhewen; Benson, Trevor M.; Jones, Chris; Earl, Simeon; Walton, Rebecca; South, Geoff (Institution of Engineering and Technology, 2018)
In this paper, the Unstructured Transmission Line Modelling (UTLM) method based on a tetrahedral mesh is applied to model the electromagnetic coupling into wire looms and bundles with multiple cores that are typical of an aircraft system, when they are exposed to plane wave illuminations. The impact on the electromagnetic coupling into wires of both bundle configuration and the positioning of the bundle relative to simple structures are investigated using the UTLM method with explicit meshing of the wires. The work not only confirms that UTLM method as a powerful tool for dealing with wire looms and bundles but provides invaluable information on the margins to be expected in key experimental waveform parameters such as peak amplitude and frequency response.